Clinical implementations of 4D pencil beam scanned particle therapy: Report on the 4D treatment planning workshop 2016 and 2017 - Trnkova, Petra; Knaeusl, Barbara; Actis, Oxana; Bert, Christoph; Biegun, Aleksandra K.; Boehlen, Till T.; Furtado, Hugo; Mcclelland, Jamie; Mori, Shinichiro; Rinaldi, Ilaria; Rucinski, Antoni; Knopf, Antje C. (Physica Medica, 2018)
In 2016 and 2017, the 8th and 9th 4D treatment planning workshop took place in Groningen (the Netherlands) and Vienna (Austria), respectively. This annual workshop brings together international experts to discuss research, advances in clinical implementation as well as problems and challenges in 4D treatment planning, mainly in spot scanned proton therapy. In the last two years several aspects like treatment planning, beam delivery, Monte Carlo simulations, motion modeling and monitoring, QA phantoms as well as 4D imaging were thoroughly discussed. This report provides an overview of discussed topics, recent findings and literature review from the last two years. Its main focus is to highlight translation of 4D research into clinical practice and to discuss remaining challenges and pitfalls that still need to be addressed and to be overcome.
EVALuna2:36473